The Relationship of Knowledge Level and Attitudes of Prospective Umrah Pilgrims with The Compliance of Meningitis Vaccination - Dwi Christina Rahayuningrum; Weni Sartiwi; Fajrihuda Yuniko (Universitas Padjadjaran, 2022)
The meningococcus vaccine is a vaccine that must be given to all people traveling to Saudi Arabia. This vaccine was needed in 2006 due to the meningococcus disease outbreak in Saudi Arabia from 1987-2003 and the disease infected pilgrims. Saudi Arabia reported an increase in the incidence of meningitis as many as 225 cases with 56 deaths, and it was reported that the number of Indonesian pilgrims was 14 cases of meningitis, with six died in Saudi Arabia. There are three people suspected of contracting meningitis during the Hajj season 2017 in West Sumatra. The Port Health Office (KKP) reported that out of 1228 total meningitis vaccination visits, 245 people (19.95%) were vaccinated less than 30 days before departure. This study aims to analyze the relationship between the level of knowledge and attitudes of prospective Umrah pilgrims with meningitis vaccination compliance. Quantitative method research with a cross-sectional research design with accidental sampling technique with a sample of 37 people at the Padang Port Health Office (KKP) in August 2019. The research instrument used a questionnaire through interviews and computerized processing techniques. The results showed that 70.3% of the Umrah pilgrims had a low level of knowledge, 54.1% of the pilgrims had negative attitudes, and 56.8% of the congregation respondents did not comply with the meningitis vaccination. It is hoped that the Padang City Port Health Office will increase the provision of information or socialization related to the timeliness of the meningitis vaccination for prospective Umrah pilgrims.